Assessing Fish Immunotoxicity by Means of In Vitro Assays: Are We There Yet? - Segner, Helmut; Rehberger, Kristina; Bailey, Christyn; Bo, Jun (Frontiers in Immunology, 2022)
There is growing awareness that a range of environmental chemicals can target the immune system of fish and may compromise the resistance towards infectious pathogens. EHowever, existing conceptsapproaches to assess chemical hazards to fish, however, do not consider potential immunotoxicity activities. Over recent years, the application of in vitro assays for ecotoxicological hazard assessment has gained momentum, what leads to and, thus, the question arises whether fish cell-based in vitro assays using piscine immune cells might would be suitable to evaluate the immunotoxic potentialsity of environmental chemicals to fish. In vitro systems using primary immune cells or immune cells lines have been established from a wide array of fish species and basically from all immune tissues, and in principal these assays should be able to detect chemical impacts on diversecould cover major immune functions. In fact, in vitro assays They were found to be a valuable tool in investigating the mechanisms and modes of action through which environmental agents interfere with immune cell functions. However, at the current state of knowledge the usefulness of thesefish cell-based in vitro assays for immunotoxicity screening in the context of chemical hazard assessment is questionable. This isuncertain, mainly because of athe lack of assay standardization, and anthe insufficient knowledge on assay perfomance with respect to false positives or false negative signals for the different toxicant groups and different immune functions. Also the predictivity of the in vitro immunotoxicity assays for the in vivo immunotoxic response of fishes is uncertain. In conclusion, is insufficient, and tthe currently available too limited database is too limited which does not to support the routine application of piscine in vitro assays as screening tool for allow to establish a tiered testing strategy covering key immune endpoints, as it exists in human immunotoxicology. Finally, if it comes to the question of the predictiveity of the in vitro immunotoxicty assays for the in vivo immunotoxic action of environmental chemcials, the current state of knowledge is clearly assessing immunotoxic potentials of environmental chemicals to fish.